A case report on the prolonged viability of postmortem human testicular sperm - Jamie Thomas, B.S; Joginder Bidhan, M.Sc; Braian Rene Ledesma, B.S; Joshua Bitran, M.D; Ranjith Ramasamy, M.D (Elsevier, 2023)
Objective: To report a case of postmortem sperm retrieval with prolonged viability and motility. Design: Case report Setting: Hospital and Medical Examiner Department Patient(s): A 44-year-old African American male patient with a history of recreational marijuana use and occasional alcohol consumption who died from a cardiac arrest because of drug overdose. Intervention(s): Multiple testicular biopsies and sperm analyses. Main Outcome Measure(s): Sperm viability and motility of testicular biopsies at serial time intervals. Result(s): Sperm obtained from the testis in the morgue remained viable and motile even at 106 hours (>4 days) postmortem. Conclusion(s): Our study found that sperm obtained from the testis remained viable and motile even after being thawed after cryopreservation, even when obtained up to 100 hours postmortem. This may have implications on the timeframe that postmortem sperm retrieval can be performed successfully several days after death.